Współczesne tendencje w zarządzaniu kadrami organizacji - Listwan, Tadeusz (Contemporary Trends in Human Resources Management of Organizations, 2008)
The main subject of this article are some tendencies in personnel function in organizations. The field of analysis is narrowed mainly to companies of western countries of Europe. The first part of the paper discusses conditions of environment influencing changes in organizations, management, and management of human resources. Next, the author presents such tendencies in personnel like: internationalization, outsourcing, talent management, virtualization, new roles of personnel managers and others. In the last part, the author discusses some changes in HRM of Polish firms. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 23-33